2016
DOI: 10.3892/ol.2016.5464
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinicopathological characteristics of colon and rectal T1 carcinoma

Abstract: Abstract. Lymph node metastasis significantly influences the management of patients with colorectal carcinoma. It has been observed that the biology of colorectal carcinoma differs by location. The aim of the current study was to retrospectively compare the clinicopathological characteristics of patients with colon and rectal T1 carcinomas, particularly their rates of lymph node metastasis. Of the 19,864 patients who underwent endoscopic or surgical resection of colorectal neoplasms at Showa University Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…In addition, female sex and the status of the muscularis mucosae were also reported as risk factors [ 22 , 31 33 ]. Regarding location, there have been several reports comparing the rectum and colon, which showed that the rate of LNM was equivalent or higher in the rectum [ 15 , 16 ]. The current study dividing the tumor location into the left- and right-side is the largest study of T1 CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, female sex and the status of the muscularis mucosae were also reported as risk factors [ 22 , 31 33 ]. Regarding location, there have been several reports comparing the rectum and colon, which showed that the rate of LNM was equivalent or higher in the rectum [ 15 , 16 ]. The current study dividing the tumor location into the left- and right-side is the largest study of T1 CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the differences in epidemiology, pathogenesis, genetic alterations, and molecular pathways between left-and right-sided advanced CRC, as well as those that divided the location of CRC into the colon and rectum [14][15][16]. However, few articles have focused on the differences in early-(T1) stage disease and divided the tumor location into the left-and right-sided colon.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for this discrepancy may be the sample investigated, since all samples from the present study were RC samples; however previous studies have included rectal and colon cancer samples. Increasing evidence reported that RC possesses numerous molecular markers and some characteristics of colon cancer (26,27). Another possible reason may be the aberrant transport process of FBI-1 protein from the cytoplasm to the nucleus, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…With recent advances in endoscopic treatments, such as ESD, many T1 CRCs can be resected endoscopically with negative margin. Although endoscopic treatment is an attractive option for the patients, T1 CRCs show approximately 10% of LNM, which requires surgical colectomy with lymph node dissection to cure the cancer (13)(14)(15)(16)(17)(18)(19)(20). Therefore, it is important to reveal the risk factors for LNM in the patients with T1 CRCs, and we should decide whether additional surgery after endoscopic resection is needed according to the presence of risk factors for LNM.…”
Section: Discussionmentioning
confidence: 99%